Microbiological impact of treatment lagoons on the economics of water for reuse in agriculture a case study in Morocco (Settat and Soualem regions). - Oubrim, N.; Ennaji, M. M.; Hajjami, K.; Bennani, M.; Hassar, M.; Cohen, N. (Cellular and Molecular Biology, 2011)
This study was undertaken to enumerate pathogens: fecal coliforms, Escherichia coli, fecal enterococci and Salmonella in the areas irrigated with treated wastewater. The samples were isolated from Settat (33°00’N, 7°37’W) and Soualem regions (34°26’N, 5°53’W). A total of (n= 48) raw water, (n=48) treated water, (n=71) of vegetables samples irrigated by treated water taken from Waste Water Treatment Plant Settat; A total of (n=24) raw water, (n=24) treated water, (n=97) of vegetables samples irrigated by treated water taken from Waste Water Treatment Plant Soualem. The results show the total average in the two stations of raw water 7.9, 6.1 log MPN 100 ml-1 for respectively fecal coliforms and E. coli, 5.4 log CFU 100 ml-1 for fecal enterococci and 5.2 log MPN L-1 for Salmonella; for treated water 4.6, 3.1 log MPN 100 ml-1 for respectively fecal coliforms and E.coli and 3.5 log CFU 100ml-1 for fecal enterococci. Regarding plants, four types of crops were harvested and analyzed (forage, herbs, cereals and vegetables), the germs charges were found with fecal coliforms, E.coli and fecal enterococci respectively 3.2, 2.8 and 4.1 log CFUg-1. Salmonella was never detected in both treated water and crops samples.